Impact of Sars-Cov-2 pandemic on hip fractures: Clinical and radiographic outcomes. (9th August 2021) - García-Seisdedos Pérez-Tabernero, Fernando; Calvo, Santiago Gabardo; Luengo-Alonso, Gonzalo; Couso, Myriam Rodríguez; Calvo, Emilio
Introduction: Hip fractures affecting older people are at a higher risk of complications during the SARS-CoV-2 pandemic. The aim of this study is to provide data about proximal femoral fractures management and early outcomes during COVID-19 pandemic compared to the same period in 2019.Material and Methods: Retrospective and comparative study performed in two different periods were analyzed: from March 15, 2020, to April 30, 2020 (the first six weeks of Spain´s current confinement) and the same period in 2019. Data regarding demographics (age and sex, housing), type of fracture, surgical performance, early outcomes (at 30 days), and at 1-year follow-up were collected. A total of 146 patients were evaluated, 89 in 2019 and 57 in 2020.Results: Despite the drop ∼35.6% in hip fractures during SARS-CoV-2 period, distribution (age ( P = 0.985), sex ( P = 0.43), housing ( P = 0.61), type of fracture ( P = 0.41)) and Charlson comorbidity index ( P = 0.12) were similar to a 2019 period. Surgical performance did not worsen in spite of the tough situation and the use of personal protective equipment, improving in some radiological variables (tip-to-apex and calcar reduction). In terms of postoperative outcomes, although there is a tendency to a short-term mortality increase (from 3.4% to 5.2%, P = 0.22), there were no differences at 1-year follow-up (20.2% in 2019 and 20.4% in 2020, P =0.587). In the same line, although in both groups the patients lost functionality at 1 year, there were no significant differences ( P = 0.42).Conclusion: Even in challenging times, protocols and adequate organization ensure proper outcomes, reaching satisfying clinical and surgical outcomes during the COVID-19 pandemic, despite an increasing trend in short term mortality not seen at 1-year follow-up.